2019
DOI: 10.1039/c9ra07516j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid catalysts based on N-heterocyclic carbene anchored on hierarchical zeolites

Abstract: N-heterocyclic carbene has been grafted on hierarchical HZSM-5 and SAPO-5 to obtain hybrid catalysts, that are active in the benzoin condensation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…With a different approach, Gianotti and colleagues also prepared N-heterocyclic carbenes (NHC) anchored hierarchical HZSM-5 (MFI topology, 10 MR, 3D aluminosilicate) and hierarchical SAPO-5 (AFI topology, 12 MR, 1D silicoaluminophosphate) and tested these acid−base hybrid materials for the benzoin condensation reaction of furfural, which is a carbene catalyzed reaction at room temperature. 427 They confirmed the successful grafting with 1 H MAS NMR, 13 C CP MAS NMR, and FTIR spectroscopy; they found that silanol groups (Si−OH) anchor NHC moieties and Brønsted acid sites are free. Moreover, they stated that these hierarchical zeolites provide good dispersion for NHC, which results in high catalytic activity and recyclability.…”
Section: Formation and Stabilization Of Carbenes In Zeolites: Supramo...mentioning
confidence: 84%
See 2 more Smart Citations
“…With a different approach, Gianotti and colleagues also prepared N-heterocyclic carbenes (NHC) anchored hierarchical HZSM-5 (MFI topology, 10 MR, 3D aluminosilicate) and hierarchical SAPO-5 (AFI topology, 12 MR, 1D silicoaluminophosphate) and tested these acid−base hybrid materials for the benzoin condensation reaction of furfural, which is a carbene catalyzed reaction at room temperature. 427 They confirmed the successful grafting with 1 H MAS NMR, 13 C CP MAS NMR, and FTIR spectroscopy; they found that silanol groups (Si−OH) anchor NHC moieties and Brønsted acid sites are free. Moreover, they stated that these hierarchical zeolites provide good dispersion for NHC, which results in high catalytic activity and recyclability.…”
Section: Formation and Stabilization Of Carbenes In Zeolites: Supramo...mentioning
confidence: 84%
“…In one of the recent studies, Buchmeiser et al showed the activity of confined cationic molybdenum imido alkylidene N -heterocyclic carbenes (NHC) complexes in SBA-15 (mesoporous silica) for olefin ring-closing metathesis reaction. With a different approach, Gianotti and colleagues also prepared N -heterocyclic carbenes (NHC) anchored hierarchical HZSM-5 (MFI topology, 10 MR, 3D aluminosilicate) and hierarchical SAPO-5 (AFI topology, 12 MR, 1D silicoaluminophosphate) and tested these acid–base hybrid materials for the benzoin condensation reaction of furfural, which is a carbene catalyzed reaction at room temperature . They confirmed the successful grafting with 1 H MAS NMR, 13 C CP MAS NMR, and FTIR spectroscopy; they found that silanol groups (Si–OH) anchor NHC moieties and Brønsted acid sites are free.…”
Section: Carbene Chemistry In Zeolite Catalysismentioning
confidence: 94%
See 1 more Smart Citation
“…Preparation of N-heterocyclic carbene (NHC) precursor and derived hybrids. [26] I-Alkylation of benzimidazole (compound 1 in Scheme 1): in a 50 mL round bottom flask kept under inert atmosphere, benzimidazole (8.5 mmol) was slowly added to a suspension of NaH (1 equiv.) in tetrahydrofuran (THF) (6 mL) at 0-5 °C under stirring; the solution was further stirred for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid catalysts, formed by organic moieties anchored onto inorganic matrices, are interesting for their capacity to combine enormous varieties of organic functional groups with a solid support with superior mechanical and thermal stabilities. Such materials offer the advantages of homogeneous catalysis, as high yields, selectivities and possible stereoselectivity, along with those of heterogeneous catalysis, with easily separable products, reduced volume of solvents and so on. Even more interesting is the possibility of using active inorganic surfaces, for instance silica with suitable concentrations of silanol groups, or silica–alumina surfaces with Brönsted and Lewis acid sites, which can in turn act as cocatalysts in cascade reactions. …”
Section: Introductionmentioning
confidence: 99%